Proceedings of the 2019 International Conference on Management of Data 2019
DOI: 10.1145/3299869.3314029
|View full text |Cite
|
Sign up to set email alerts
|

Towards Democratizing Relational Data Visualization

Abstract: The problem of data visualization is to transform data into a visual context such that people can easily understand the significance of data. Nowadays, data visualization becomes especially important, because it is the de facto standard for modern business intelligence and successful data science. This tutorial will cover three specific topics: visualization languages define how the users can interact with various visualization systems; efficient data visualization processes the data and produces visualization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…In this work, we present initial steps towards an end-to-end performance benchmark for interactive, real-time querying scenarios, derived from user study data that we collected for crossfilter contexts (a representative of dynamic queries). Our benchmark design is inspired by recent proposals [6,17] and tutorials [28,29,61] across multiple communities, and incorporates methodology from HCI, visualization, and databases. We ran our benchmark with 128 workflows and five different DBMSs, and found that none of these systems could adequately support our benchmark workload for datasets considered far from large in the database community.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this work, we present initial steps towards an end-to-end performance benchmark for interactive, real-time querying scenarios, derived from user study data that we collected for crossfilter contexts (a representative of dynamic queries). Our benchmark design is inspired by recent proposals [6,17] and tutorials [28,29,61] across multiple communities, and incorporates methodology from HCI, visualization, and databases. We ran our benchmark with 128 workflows and five different DBMSs, and found that none of these systems could adequately support our benchmark workload for datasets considered far from large in the database community.…”
Section: Discussionmentioning
confidence: 99%
“…Recent vision papers [7,17] and tutorials [28,29,61] discuss these issues, and propose initial directions on how to design DBMSs to better support real-time interactive workloads (e.g., [17]). However, to the best of our knowledge, this paper is the first to derive a database benchmark completely based on real traces of user interactions.…”
Section: Performance Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The apparent accuracy of representations on a graph about Covid-19 or about electoral results, to mention some recent examples, may conceal errors that yield misleading results, which often go unnoticed by the authors themselves. These may be due to problems with backup data, or source data, with which there may be issues because of bias, because they are incomplete or because they have been wrongly combined (Tang;Wu;Li, 2019), and what are known as dirty data (Kim et al, 2003) which require tools and verification processes (Kasica;Berret;Munzner, 2020).…”
Section: Making the Invisible Accessible And Visible Limitations And Problemsmentioning
confidence: 99%
“…Researchers have long considered the application of neural nets to data management problems, including learning indices [16], query optimization, data cleaning and entity matching [20,23,32]. In applying neural networks to data management, research has so far assumed that the data was modeled by a database schema.…”
Section: Introductionmentioning
confidence: 99%